Aktivitas Ibu-ibu Rumah tangga di Luar Rumah Terhadap Pembinaan Anak dalam Keluarga di Negeri Tulehu Pulau Ambon - MS Darakay (JURNAL PERTANIAN KEPULAUAN, 2020)
In the family, the mother serves very dominantly, not only taking care of the family and household activities but also helping the family economy. It is their effort to achieve a prosperous family. Children's learning is one of the characteristics of family welfare. If the child's learning is well fulfilled, it is a form of family welfare. The aims of this research were (1) to study and draw outdoor activities of the housewives, particularly in agribusiness and social organization, (2) to study the impact of women's multiple roles on children raising in the family. The research was conducted using a structured interview method, where data were collected and analyzed both quantitatively and qualitatively using the cross-tabulation technique to show the correlation between variables. The results showed that, in general, housewives who spent more work hours and workdays outdoor were more effective in raising children.